Keefektifan Model Pembelajaran Kontekstual dengan pendekatan open ended dalam aspek penalaran dan pemecahan masalah pada materi segitiga di kelas VII. - Sulianto, Joko (MALIH PEDDAS, 2011)
Abstrak The Education Unit Level Curriculum states that problem solving, reasoning is the goal of learning mathematics elementary, junior high school and vocational school in addition to goals related to understanding the concept, this is contrary to the conditions of teachers who assume that the final answer to these problems is the main goal in learning , the procedure less students in solving the problems noted by teachers as too oriented to the truth of the final answer. Such conditions require the learning of mathematics with emphasis on problem-solving process. This study is an experimental study to analyze the effectiveness of contextual learning with open-ended approach in reasoning and problem-solving aspect of the triangle of material in class VII. Issues that were examined: 1) Do students who get contextual learning with open-ended approach can achieve exhaustiveness learn?, 2) Does problem-solving skills of students who get contextual learning with open-ended approach is better than in students with learning expository method?, 3) Is the reasoning that students can reach the criterion was after getting contextual learning with open-ended approach?. The study population was all students in grade VII Kesatrian SMP 2 Semarang. The sample study was graders VIIa as an experimental class and grade students VIIE as a control class. The variables studied are the reasoning and problem-solving. Data obtained from the documentation, testing and observation. The data obtained were analyzed using average test, correlation, analysis dwifaktor, and t-test. Results showed that students can achieve exhaustiveness study with an average of 73.31, t value = 3.137 with p value = 0.003 <0.05 means that student learning outcomes are significantly> 65. Reasoning students showed 33.33% of students have demonstrated high reasoning, 38.88% students have a reasoning being, and 27% of students have low reasoning sig later than table value 0.000 <0.05 with a mean value of r = 0.745 reasoning and problem solving has ties are very strong at 74.5%. Problem-solving abilities of students with contextual learning and open ended approach is different from expository teaching classes, based on the t test with a test value 0.030 p value <0.05. Average problem solving abilities of students reached 73.3 while the control class 65, 83 meaning that the average problem solving abilities of students in a class of contextual learning with open-ended approach is better. Then seen from the test value v dwifaktor test value 0.178 means not different problem-solving skills of students seen from the top, the middle and bottom groups. Concluded that the contextual learning with open-ended approach in reasoning and problem-solving aspect of the triangle of material in class VII learn effectively and achieve completeness. Keywords: Effectiveness, contextual learning, open ended, reasoning, problem-solving.